Allergological in vitro and in vivo evaluation of patients with hypersensitivity reactions to infliximab. Issue 6 (28th May 2013) - Matucci, A.; Pratesi, S.; Petroni, G.; Nencini, F.; Virgili, G.; Milla, M.; Maggi, E.; Vultaggio, A.
Summary Background The administration of biological agents is potentially affected by IgE‐mediated infusion reactions. Objective The aim of the study was to evaluate the utility of skin testing in patients who have experienced infliximab (IFX)‐related reactions. Methods Thirty patients with previous immediate hypersensitivity reaction to IFX, 20 disease‐matched non exposed subjects, 15 IFX‐treated disease‐matched tolerant patients and 15 IFX non‐responder patients were enrolled. Non‐isotype‐specific and IgE anti‐drug antibodies (ADAs) were measured by a double‐capture ELISA kit and ImmunoCAP assay, respectively. Prick and intra‐dermal tests were carried out with the commercial IFX preparation serially diluted. Results Skin testing, performed in 23 of 30 reactive patients, resulted positive in 7 of them (30.4%), whereas no positivity was found in other groups of patients. The majority of reactive patients displayed non‐isotype‐specific ADAs (23/30, 76.6%) and the presence of anti‐IFX IgE antibodies was detected in 6 of them (26%). All 6 IgE‐positive reactive patients showed skin testing positivity. One reactive ADAs‐positive patient who resulted skin test positive, with no detectable serum IFX‐specific IgE ADAs, was also found. Skin testing positivity was associated with severe and early reactions (within the 3rd dose). No unexpected adverse reactions to skin testing were recorded. Conclusions and Clinical Relevance This study shows that about 30% of reactive patients display skin testing positivity. They usually develop severe reactions, mainly during the first administrations of IFX. The specificity and the safety of skin testing procedure for this biological agent are also confirmed.